PENGARUH SELEKSI DAN PENEMPATAN TERHADAP KINERJA KARYAWAN PADA PT. SWADHARMA SARANA INFORMATIKA PEKANBARU - Fitrianti, Rossy; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at the PT. Swadharma Sarana Informaika Pekanbaru at Jalan Kutilang No. 09 Kampung Melayu Sukajadi, Kota Pekanbaru. The purpose of this study is to determine and analyze the influence of selection and placement on employee performance parttially and simultaneously. This study uses a questionnaire as a data collection tool that is distributed to 67 respondents to employees of PT. Swadharma Sarana Informatika Pekanbaru. The data is then processed using descriptive analysis and quantitative analysis using SPSS by conducting validity, realibity testing, simple linear regression analysis, multiple linear regression analysis, determination analysis (R2) and hypothesis testing byÂ Â t (partial) and F (simultaneous) testing. The results showed that the first hypothesis testing which is selection on employee performance was tcount (2,087) > ttable (2,000), meaning that selection significantly influenced employee performance. Second placement of employee performance is tcount (3,062) > ttable (2,000), meaning that placement has a significant effect on employee performance. The result of Fcount (8,125) > Ftable (3,15) means that selection and placement have a significant effect on employee performance.Â Keywords: Selection, Placement, Employee Performance